Determinants of Total Deposit Growth in Philippine Banking: A Statistical Study Across Banking Groups - Jess Andes; Anne Lorraine L. Abanto; Edward Louie Y. Abejero; Ginesa C. Anticuando; Ira Faye N. Apay; Jella O. Bacatan; Marvin Ian E. Niere; Peter G. Narsico (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This paper analyzes the drivers of total deposit growth in the Philippine banking system for years 2014-2024. It considers the joint impact of macro-economic conditions and technology development across the major banking groups. The study utilized a descriptive-correlational design and secondary data were obtained from the Bangko Sentral ng Pilipinas and the Philippine Statistics Authority. The correlation analysis was performed to study the correlation between the macroeconomic and technological variables and the deposit growth. The results show that total deposits are still growing mainly driven by the Universal and Commercial Banks. GDP, GDP per capita, CPI and digital payment adoption are very strongly positively related to deposit growth while PPP is very strongly negatively related showing that nominal deposits grow when purchasing power falls. Of the variables that point to financial technology’s growing importance, digital payments have the highest correlation across banking groups. “There are differences between bank types. Larger banks are more sensitive to macroeconomic and technological factors. The findings show that economic performance and digital transformation have a significant relationship with the growth of deposits in the Philippine banking industry. Macro-economic stability is the structural basis for deposit mobilization. But the biggest innovation related to the growth of deposits of financial inclusion and expansion of deposits is digital innovation. The results suggest that policymakers and financial institutions could consider integrated approaches to improve economic fundamentals, while encouraging digital financial infrastructure to facilitate the development of the banking sector.